Influence of Water Deficit on Transpirational and Water Relation Parameters in Wheat - Srivastava, J P; Chaturvedi, S N (Annals of Arid Zone, 2016)
Potted plants of wheat cv Â·C-306' (drought resistant) and 'Kalyan sona' (relatively drought susceptible) were compared for various transpirational parameters under moisture stress. Differences in transpiration rates were narrower in the control and in stressed plants of 'C-306' than in 'Kalyan sona'. The difference of leaf to air temperature was higher in 'Kalyan sona'. Abaxial to adaxial leaf conductance ratio increased in both the varieties under severe slress condition. Correlations between various components of water relation and transpiration in the two cultivars are discussed.